Theory of storage: an empirical assessment of the European natural gas market - Marcus Stronzik; Margarethe Rammerstorfer; Anne Neumann (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
We analyze the relation between European natural gas storage facilities and price patterns at major trading points, considering the theory of storage to derive a testable hypothesis imposed by the non-arbitrage condition. To model the efficiency of the natural gas market, we apply two indirect tests absent the scarcity of European inventory data. We find that operators of storage facilities realize seasonal arbitrage profits, and that market performance overall is substantially distinct from the competitive benchmark.
Keywords: Q40; L95; G13; 330; Storage; energy commodity; natural gas; convenience yield; Erdgas; Lager; Erdgasmarkt; Preis; Rohstoff-Futures; EU-Staaten